Participatory sport events in times of COVID-19: analysing the (virtual) sport behaviour of event participants. Issue 1 (2nd January 2022) - Helsen, Kobe; Derom, Inge; Corthouts, Joris; Bosscher, Veerle De; Willem, Annick; Scheerder, Jeroen
ABSTRACT: Research question: Due to government restrictions because of COVID-19, all participatory sport events (PSEs) were cancelled. As a result, knowledge is needed as to how and to what extent participants of PSEs modified their sport behaviour to fill the void of event cancellation. Therefore, this study aimed to (1) investigate to what extent event participants have modified their sport behaviour as a result of the COVID-19 measures, and (2) analyse the factors that determine participation in virtual events (real activities using an online recording platform). Research methods: A total of 2869 respondents completed an online survey which was widely disseminated in Flanders (Belgium) six weeks after the announcement of the COVID-19 lockdown. The sample included both event and non-event participants. Descriptive and binary logistic regression analyses were used to investigate how event participants adapted their sport behaviour and which factors determined virtual event participation. Results and findings: Since the COVID-19 measures, event participants did not decrease the frequency but only the intensity of their sport behaviour. Based on social ecological theory, participation in virtual events could be explained by both individual determinants (e.g. motivation towards developing skills), and interpersonal determinants (e.g. previous participation in a virtual event). Implications: This study contributes to research on the impact of COVID-19 measures and consequently the cancellation of PSEs on sport behaviour of event participants. Confronted with an uncertain future, the findings provide insights for event organisers to develop and optimise virtual event experiences in order to reach non-event participants as well.